Journalistic Treatment of Violations of Iraqi Women’s Rights: An Analytical Study of Al-Sabah Newspaper from 1st July 2021 to 31st December 2021 - Ali, Yusra Hamza; Al-Sarraj, Shakiria Kawkaz (ALBAHITH ALALAMI, 2023)
This research examines how Al-Sabah newspaper addressed violations of women’s rights in Iraq. Using content analysis, a sample of 157 articles published from July 1, 2021, to December 31, 2021, was analyzed. The study reveals diverse journalistic treatments, with interpretive approaches employed in addressing violations of Iraqi women’s rights. Social violations of women’s rights were the primary focus, and various forms of newspaper articles, including opinion pieces, were commonly used.